2002
DOI: 10.1063/1.1469693
|View full text |Cite
|
Sign up to set email alerts
|

Electrical isolation of p-type GaAs layers by ion irradiation

Abstract: The electrical isolation of p-type GaAs layers doped with acceptor impurities incorporated in the Ga sublattice ͑Mg͒ or As sublattice ͑C͒ was studied using proton bombardment. It was found that practically the same proton dose is required to reach complete isolation ͑isolation threshold dose, D th ͒ in layers doped with either Mg or C of comparable original sheet hole concentration (p s ). This result is evidence that the sublattice where the acceptor dopant atoms are incorporated does not play any significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The sheet resistance reaches a narrow plateau when the concentration of deep levels is of the same magnitude as the free hole concentration, and is determined by the sheet resistance of the underlying SI GaAs substrate. 1,2,[7][8][9][10]15,16 Any further increase in dose beyond this plateau results in the monotonic decrease in R s ͑closed circles͒ because of hopping conduction of holes between closely spaced defect potential wells. 18 Following Ref.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sheet resistance reaches a narrow plateau when the concentration of deep levels is of the same magnitude as the free hole concentration, and is determined by the sheet resistance of the underlying SI GaAs substrate. 1,2,[7][8][9][10]15,16 Any further increase in dose beyond this plateau results in the monotonic decrease in R s ͑closed circles͒ because of hopping conduction of holes between closely spaced defect potential wells. 18 Following Ref.…”
Section: Methodsmentioning
confidence: 99%
“…This is because the vacancies are precursors for the creation of antisite defects. The choice of the total number of replacements stems partially from the recent discussion of Boudinov et al 16 that the defect responsible for the isolation in p-type GaAs is the double-donor arsenic-antisite, As Ga , and the results discussed below. By including the data point for 0.1 MeV H ions in Fig.…”
Section: A Effect Of Ion Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Going from the recoil stop to the eletric conductivity it must be taken into account that the resistivity increases strongly non-linearly with the defect distribution, as discussed before, thus giving a strongly non-linear dependence of etching rate and proton fluence. The experimental values of the correlation between defect concentration and resistivity measured by Boudinov et al [20] may be directly mapped to the values shown in Fig. 2 by taking into account the material's original resistivity and the proton fluence, thus yielding conductivity distributions as shown in Fig.…”
Section: Conductivity Mapsmentioning
confidence: 99%
“…Many studies have been carried out in order to understand the nature of such defects leading to insulating GaAs and their influence on the electrical properties of irradiated GaAs substrates [8], [14], [16]- [19]. The decrease in conductivity, and in our particular electrochemical etching case the decrease in hole conduction, has been shown to be due to trapping of holes at specific trap centers [18], [20]. Such traps are created due to nuclear energy loss and it is thus obvious to relate the experimental defect production rate to the one calculated with e. g. SRIM [21], as shown in the past.…”
Section: Introductionmentioning
confidence: 99%